Interactions between adjacent ganglia bring about the bilaterally alternating differentiation of RAS and CAS neurons in the leech nerve cord - Blair, SS (J Neurosci, 1990)
Antibodies to small cardioactive peptide (SCP) label a segmentally iterated subset of cells in the leech nerve cord, including the previously identified alternating SCP (AS) neurons. Unlike the majority of leech neurons, these cells are asymmetrically distributed in the adult nerve cord. Moreover, each AS neuron shows a strong tendency to lie on alternate right and left sides in successive ganglia. Previous work has shown that these unpaired neurons arise from bilaterally paired embryonic homologues, only 1 of which takes on the mature immunoreactive phenotype. The 2 AS homologues within a ganglion compete for this fate, in that either the right or the left homologue will become a mature AS neuron with a high degree of reliability if its contralateral homologue is ablated during embryogenesis. In this paper, we demonstrate the existence of interactions between neurons in adjacent ganglia that could account for the alternation of sides observed during normal development. The unilateral ablation of a single AS homologue neuron forced its contralateral homologue to take on the mature AS fate, and this consistently biased the side of AS development in adjacent, unlesioned ganglia both anterior and posterior to the lesion. One of the AS neurons, the caudal alternating SCP (CAS) cell, was injected with Lucifer yellow in adult nerve cords and was shown to have a large primary axon that extends into more anterior ganglia, as well as other, finer axons that are variable in number and arrangement. If the interganglionic interaction of AS neuron homologues is mediated by their primary axons, signals of developmental import must be transmitted both anterogradely and retrogradely along the axon's length. The present results indicate that the development of individual AS neurons is influenced by homologous cells located in the same and neighboring ganglia and suggest that the final, multisegmental patterning of the AS neuron distribution is not predetermined, but rather, arises as an emergent property of the cell interactions that occur during nervous system differentiation.